2022
DOI: 10.1002/advs.202202684
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development and Antimicrobial Applications of Metal–Phenolic Networks

Abstract: Due to the abuse of antibiotics and the emergence of multidrug resistant microorganisms, medical devices, and related biomaterials are at high risk of microbial infection during use, placing a heavy burden on patients and healthcare systems. Metal-phenolic networks (MPNs), an emerging organic-inorganic hybrid network system developed gradually in recent years, have exhibited excellent multifunctional properties such as anti-inflammatory, antioxidant, and antibacterial properties by making use of the coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 185 publications
1
54
0
1
Order By: Relevance
“…For TEC, as shown in Figure S10 (Supporting Information), when the concentrations were <50 µg mL −1 , the cell viabilities of L929 were all higher than 80%. These results indicated that Eu 3+ and TEC are cytocompatible in a reasonable range, in accordance with the cytocompatibility results of europium hydroxide nanorods [56] and other MPNs. [70] The cytocompatibility of TE-TCMBAs was evaluated by investigating the cytotoxicity of the sol contents and degradation products of TE-TCMBAs via CCK-8 and Live/Dead assay against L929 and human umbilical vein endothelial cells (HUVECs).…”
Section: In Vitro Cell Cytocompatibility Cell Proliferation Migration...supporting
confidence: 84%
See 1 more Smart Citation
“…For TEC, as shown in Figure S10 (Supporting Information), when the concentrations were <50 µg mL −1 , the cell viabilities of L929 were all higher than 80%. These results indicated that Eu 3+ and TEC are cytocompatible in a reasonable range, in accordance with the cytocompatibility results of europium hydroxide nanorods [56] and other MPNs. [70] The cytocompatibility of TE-TCMBAs was evaluated by investigating the cytotoxicity of the sol contents and degradation products of TE-TCMBAs via CCK-8 and Live/Dead assay against L929 and human umbilical vein endothelial cells (HUVECs).…”
Section: In Vitro Cell Cytocompatibility Cell Proliferation Migration...supporting
confidence: 84%
“…[25] In addition, TA or phenolic groups can also chelate with metal ions (such as Ag + , Fe 3+ , Al 3+ , and Cu 2+ ) to form metal-phenolic networks (MPNs) or metal-phenolic coordination polymers (MPCPs). [53][54][55][56] Among metal ions, europium (Eu, a rare earth metal) ions have attracted increasing attention due to its angiogenesis promotion activity. [54,57,58] Furthermore, the metal-phenolic coordination bonds tend to disintegrate under acidic conditions caused by the competition of phenolic groups between protons and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the inherent deep penetration, noninvasiveness, and local site targeting properties, the near-infrared (NIR)-responsive photothermal therapy (PTT) offers a promising alternative for antibacterial wound dressing fabrication. Photothermal-active materials such as metallic compounds, carbon nanomaterials, and organic dye have been completely studied for biomedical treatments. However, their applied exploration is limited by the high cost, tedious synthesis, low biocompatibility, and low biodegradation. Recently, metal-phenolic networks (MPNs) have been well studied to serve as a PTT platform owing to low cost and good biocompatibility. The fabrication of MPNs was mainly based on the chelation between metal ions and the catechol structure. It suggests that the utilization of polyphenol compounds and metal ions may offer an approach to the development of new photothermal materials.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, metal-phenolic networks (MPNs), a type of supramolecular structure, are composed of polyphenols and metals via the coordination of the diverse phenolic ligands on polyphenols and metals (Geng et al, 2022;. Involving in various polyphenols derives, metal with therapeutic and imaging properties, biofunctional agents endow a large library of MPNs with charming functions (Dai et al, 2019;Y. Li, Miao, et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, metal‐phenolic networks (MPNs), a type of supramolecular structure, are composed of polyphenols and metals via the coordination of the diverse phenolic ligands on polyphenols and metals (Geng et al, 2022; J. Guo et al, 2016). Involving in various polyphenols derives, metal with therapeutic and imaging properties, biofunctional agents endow a large library of MPNs with charming functions (Dai et al, 2019; Y. Li, Miao, et al, 2022; Y. Li, Zhang, et al, 2022). Hence, MPNs have attracted much concern in the application of bioimaging and biomedicine due to their facile functionalization, pH‐sensitive drug release, good biocompatibility (Ejima et al, 2017; Ju et al, 2022).…”
Section: Introductionmentioning
confidence: 99%